Everyday life transmitted in cyberspace: The phenomenon of lifecasting (2011)
This paper presents some reflections and results about research on communication processes in the digital context -- It also presents the implications of different registration and publication forms in daily life in the constitution of other modes of visibility, that allows to talk about concepts such as life online -- Thus, this work will show the different ways of exposure patterns of daily life and its place in the language configuration, the spatial dynamics and relationships with others, to characterize a specific mode of entry into everyday life line called lifecasting -- Finally, from the emerging phenomenon called lifegoing, the text aims a road for an investigation program about whats called: visibility technology’s -- A field that demands the articulation of humanistic knowledge as reference of thinking in the technological improvements, and their aestetic and political implications in the field of what it’s known as socio-technical-cultural studies (STCS)